Breathing Biofeedback for Police Officers in a Stressful Virtual Environment: Challenges and Opportunities - Brammer, Jan C.; van Peer, Jacobien M.; Michela, Abele; van Rooij, Marieke M. J. W.; Oostenveld, Robert; Klumpers, Floris; Dorrestijn, Wendy; Granic, Isabela; Roelofs, Karin (Frontiers in Psychology, 2021)
As part of the Dutch national science program "Professional Games for Professional Skills" we developed a stress-exposure biofeedback training in virtual reality (VR) for the Dutch police. We aim to reduce the acute negative impact of stress on performance, as well as long-term consequences for mental health by facilitating physiological stress regulation during a demanding decision task. Conventional biofeedback applications mainly train physiological regulation at rest. This might limit the transfer of the regulation skills to stressful situations. In contrast, we provide the user with the opportunity to practice breathing regulation while they carry out a complex task in VR. This setting poses challenges from a technical- (real-time processing of noisy biosignals) as well as from a user-experience perspective (multi-tasking). We illustrate how we approach these challenges in our training implementation and hope to contribute a useful reference for researchers and game developers in academia or industry who are interested in using biosignals to control elements in a dynamic virtual environment.